THE IMPACT OF SOCIAL NETWORKS ON THE CHANGE IN THE SPIRITUAL IMAGE OF YOUNG PEOPLE - Akhmedova Dilrabo Sa’dullayevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Since social networks have become a powerful weapon of information today, they have become an important factor in the promotion and propaganda of ideological and ideological threats around the world. With the help of social networks, special attention is paid to the influence on the soul, consciousness, and psyche of young people. As a result of this, the spirituality of young people leads to disarray. Therefore, we should not ignore the escalation of various ideological, ideological, and information attacks. Only then, in the future, we will achieve the upbringing of a spiritually harmonious person, a healthy generation. In this article, opinions and comments are made about the impact of social networks on the change in the spiritual image of young people.